Exosomes as the source of biomarkers of metabolic diseases - Lee, Min-Jae; Park, Dong-Ho; Kang, Ju-Hee (Annals of pediatric endocrinology & metabolism, 2016)
Exosomes are extracellular vesicles that contain molecules that regulate the metabolic functions of adjacent or remote cells. Recent , and clinical studies support the hypothesis that exosomes released from various cell types play roles in the progression of metabolic disorders including type 2 diabetes. Based on this concept and advances in other diseases, the proteins, mRNA, microRNA and lipids in exosomes isolated from biological fluids have been proposed as biomarkers in metabolic disorders. However, several problems with the development of clinically applicable biomarkers have not been resolved. In this review, the biologic functions of exosomes are briefly introduced, and we discuss the technical and practical pros and cons of different methods of exosome isolation for the identification of exosomal biomarkers of metabolic disorders. Standardization of preanalytical variables and isolation of high-purity exosomes from fully characterized biological fluids will be necessary for the identification of useful exosomal biomarkers that can provide insights into the pathogenic mechanisms of complications of metabolic syndrome and of whole-body metabolism.